Biological research on the occurrence and development of multiple myeloma and its treatment - Yue Wu; Xiangjun Shi; Xinchen Yao; Xinru Du (Immunity, Inflammation and Disease)
Abstract Introduction To review the pathogenesis and treatment of multiple myeloma (MM). MM is a hematological malignancy with abnormal plasma cell proliferation in bone marrow. Due to the emergence of drug resistance, MM is still an incurable malignancy, which requires further exploration of pathogenesis and effective therapeutic targets. Methods In this paper, the method of literature review is adopted to obtain the information about MM. Based on the literature, comprehensive and systematic review is made. Results MM is a complex pathophysiological process with great heterogeneity, mainly reflected in genomic instability and bone marrow microenvironment. At present, the treatment of MM has made great progress, proteasome inhibitors and immunomodulatory drugs are widely used in clinic. Allogeneic stem cell transplantation may be the only promising cure for MM, and its high transplant‐related mortality limits its clinical application. Conclusions The future of MM treatment lies in the development of more targeted therapies, novel immunotherapies, and a better understanding of the disease's molecular and genetic basis.